2014
DOI: 10.1016/j.molcel.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Signals through ATF6 and PERK to Promote Endothelial Cell Survival and Angiogenesis in the Absence of ER Stress

Abstract: Accumulation of unfolded proteins in the endoplasmic reticulum (ER) initiates IRE1α, ATF6, and PERK cascades, leading to a transcriptional/translational response known as unfolded protein response (UPR). Here we show that VEGF activates UPR mediators through a PLCγ-mediated crosstalk with the mTORC1 complex without accumulation of unfolded proteins in the ER. Activation of ATF6 and PERK contributes to the survival effect of VEGF on endothelial cells (ECs) by positively regulating mTORC2-mediated phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
141
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 49 publications
7
141
0
Order By: Relevance
“…It is tempting to speculate that macropinocytosis might be responsible for delivering signalling complexes of the receptor to downstream targets, such as ERK1/2 and Akt, that could reside at specific endosomal compartments (Dobrowolski and De Robertis, 2012;McKay and Morrison, 2007;Miaczynska et al, 2004;Platta and Stenmark, 2011;Schenck et al, 2008;Sorkin and von Zastrow, 2009;Teis et al, 2002;Zouggari et al, 2009). Consequently, macropinocytosis would link VEGFR2 to the downstream cascades required to regulate complex angiogenic responses, such as survival (Karali et al, 2014), proliferation and migration of endothelial cells (Herbert and Stainier, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that macropinocytosis might be responsible for delivering signalling complexes of the receptor to downstream targets, such as ERK1/2 and Akt, that could reside at specific endosomal compartments (Dobrowolski and De Robertis, 2012;McKay and Morrison, 2007;Miaczynska et al, 2004;Platta and Stenmark, 2011;Schenck et al, 2008;Sorkin and von Zastrow, 2009;Teis et al, 2002;Zouggari et al, 2009). Consequently, macropinocytosis would link VEGFR2 to the downstream cascades required to regulate complex angiogenic responses, such as survival (Karali et al, 2014), proliferation and migration of endothelial cells (Herbert and Stainier, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding to VEGFR on endothelial cells, VEGF activates the UPR sensors through the phospholipase Cg (PLCg) pathway without accumulation of misfolded proteins in the ER (59). This, in turn, promotes endothelial cell survival in an AKT-dependent manner and induces angiogenesis in mouse models (59).…”
Section: Er Proteostasis Control In Glioma Stromal Cells Gliomas Reprmentioning
confidence: 99%
“…Upon binding to VEGFR on endothelial cells, VEGF activates the UPR sensors through the phospholipase Cg (PLCg) pathway without accumulation of misfolded proteins in the ER (59). This, in turn, promotes endothelial cell survival in an AKT-dependent manner and induces angiogenesis in mouse models (59). In addition, more recent work showing that signal transducer and activator of transcription 3 (STAT3)-or STAT6-activating cytokines yield predominantly IRE1-mediated cathepsin expression and secretion suggests that UPR activation in TAMs contributes to cancer invasion (125).…”
Section: Er Proteostasis Control In Glioma Stromal Cells Gliomas Reprmentioning
confidence: 99%
“…Genetic studies have demonstrated that PERK is essential in supporting tumor growth and progression via diverse mechanisms, including stimulation of angiogenesis (7)(8)(9)(10)(11)(12), potential effects on antitumor immunity (13,14), and direct increase in cancer cell viability by altering its metabolic status (15), promoting survival autophagy (16)(17)(18), and induction of prosurvival microRNAs (19). Accordingly, development of novel, potent, and selective PERK inhibitors as a means to treat cancers has been proposed (20,21).…”
mentioning
confidence: 99%